Training of Adult Trainers: Implementation and Evaluation of a Higher Education Program in Greece - Mavropoulos, Azarias A; Sipitanou, Aikaterini; Pampouri, Anastasia (International Review of Research in Open and Distributed Learning, 2019)
This article presents the implementation and the evaluation of the blended learning program Training of Lifelong Learning Adult Trainers, which was organized by the Center of Training and Lifelong Learning of the Aristotle University of Thessaloniki in Greece, during the last two years (2016-2017). The aim of the training program was to give the opportunity to adult trainers to certify their educational competence and update their knowledge in the field of adult education, enhancing their employability. After the completion of the program, the trainees assessed the implementation methodology, the educational content, the microteachings, the quality, and the organization of the program. The results of the evaluation showed that the program was of a high level, flawlessly organized, and with excellent educational material, while the blended learning model worked effectively, receiving positive reviews by the participants. It was concluded that blended learning is indeed adequate in adult educational programs increasing the participation and facilitating adult trainees to better integrate their learning experiences.